A novel LNG-IUS suture fixation method utilizing the hysteroscopy cold knife system: nail-type anchoring suture - Duan, Duan; He, Li; Zhang, Chengling; Hou, Qiannan; Cao, Qinyan; Xiong, Ying (Frontiers in Medicine, 2026)
BackgroundThe levonorgestrel intrauterine system (LNG-IUS) may have its contraceptive or therapeutic efficacy compromised if displacement or expulsion occurs. By suturing and securing the device to the uterine wall, the risk of expulsion can be significantly reduced. This approach ensures sustained contraceptive and therapeutic effects, particularly for patients with larger uterine volumes or a history of IUD displacement.MethodsOur team delineated the material selection criteria, operating system, and instrument configuration plan for LNG-IUS nail-type anchoring suture surgery via a clinical case, and illustrated the surgical operation steps in detail.ResultsThrough comparative analysis of patients' preoperative and postoperative conditions, integrated with intraoperative imaging and postoperative ultrasonographic data, this study confirms that the innovative nail-type suture technique for LNG-IUS has demonstrated the intended efficacy. It exhibits significant clinical utility, offering an efficacious therapeutic option for patients presenting with abnormally enlarged uterine cavities or recurrent LNG-IUS displacement or expulsion.ConclusionsOur team pioneered the innovative development of the nail-type anchoring suture technique. This approach departs from conventional suturing methodologies and existing modified fixation techniques. It achieves robust anchoring while obviating the necessity for hysteroscopic visualization during ring removal. This significantly improves clinical outcomes and yields substantial economic advantages.